Upaya Perlindungan Hukum Bagi Korban Kekerasan Seksual Pada UU No 12 Tahun 2022 - Tasya Putri Afrudi; Asep Suherman (CV. ITTC INDONESIA, 2024)
Sexual violence is something that often occurs in society in Indonesia, sexual violence occurs regardless of place, so the incident is often heard, but the enforcement of penalties against the perpetrator is not firm, so legal protection efforts against victims of sexual violence are often not enforced. Therefore, the purpose of this research is to find out how efforts to protect victims of sexual violence in Law No. 12 of 2022 on criminal acts of sexual violence. This research uses normative legal research methods with a legal approach. The results of this study show how legal design as an effort to resolve cases of sexual violence and protection from sexual harassment.